Zombieland double-tap [videorecording (DVD)] - Deutch, Zoey, 1994-; Stone, Emma, 1988-; Breslin, Abigail, 1996-; Murray, Bill, 1950 September 21- (Sony Pictures Home Entertainment, 2020)
Through comic mayhem that stretches from the White House and through the heartland, Columbus, Tallahasse, Wichita, and Little Rock must face off against the many new kinds of zombies that have evolved since the first movie, as well as some new human survivors. But most of all, they have to face the growing pains of their own snarky, makeshift family.